Do the Teachers Who Are Selected by Students Have a Higher Emotional Intelligence? - Fariba Haghani; Bahareh Aminian; Tahereh Changiz (Kerman University of Medical Sciences, 2012)
Background & Objective: In order to achieve an efficient teaching in all fields including Medicine effective teachers are needed and to evaluate the efficiency of teachers students comments are a remarkable indicator Since during the recent decades Emotional Intelligence has been mentioned as one of the characteristics of distinguished teachers this study aimed to investigate the emotional intelligence and its components among professors of basic sciences level of Medicine field selected as distinguished teachers by senior students in comparison to other professors in this level Methods: In this descriptive study all Medicine students of the selected university in the final semester of basic sciences phase (n=65) were asked to name their five top distinguished teachers Finally 8 teachers who had the highest votes were considered as the distinguished group To assess teachers emotional intelligence the standard questionnaire of BarOn is distributed among all teachers of basic sciences (53 cases) and their emotional intelligence in 15 different components was evaluated Data were analyzed through SPSS software and by using correlation and independent ttest Results: Mean total score of Emotional Intelligence of distinguished teachers (35213) was higher compared to that of the other teachers (33788) but the difference was not significant The scores of distinguished group in the subscales of happiness optimism selfconfidence and flexibility were significantly higher compared to the other teachers (P